REAL-TIME AIR POLLUTION MONITORING AND CONTROLLING SYSTEM - Kurani, Prachit; Shah, Yash (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This paper presents Real-Time system for air pollution monitoring and control. The main objective of the work is designing microcontroller based toxic gas detecting and alerting system. This is a semi-automated system such that if the pollution level exceeds the normal level then an alarm is generated immediately and also an alert message (SMS) is sent to the authorized person through the GSM. Along with this the ionizer responsible for reducing the level of pollutants too would be started by the system. Time to time detected data would be stored into database for further retrieval.